2015
DOI: 10.1016/j.neuropharm.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The GABAB receptor positive modulator BHF177 attenuated anxiety, but not conditioned fear, in rats

Abstract: GABAB (γ-aminobutyric acid B) receptors may be a therapeutic target for anxiety disorders. Here we characterized the effects of the GABAB receptor positive allosteric modulator (PAM) BHF177 on conditioned and unconditioned physiological responses to threat in the light-enhanced startle (LES), stress-induced hyperthermia, and fear-potentiated startle (FPS) procedures in rats. The effects of BHF177 on LES were compared with those of the GABAB receptor agonists baclofen and CGP44532, and the positive control busp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Very similar results were obtained with other positive GABAB receptor modulators such as CGP7930 [20], ADX1441 [19] or BHF117 [24,27]. However, in some anxiety tests, the positive GABA B receptor modulators had no effects on anxiety-like behavior [18,20,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Very similar results were obtained with other positive GABAB receptor modulators such as CGP7930 [20], ADX1441 [19] or BHF117 [24,27]. However, in some anxiety tests, the positive GABA B receptor modulators had no effects on anxiety-like behavior [18,20,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, many studies showed anxiolytic-like properties of GS39783, one of the first positive GABA B receptor modulators, in a variety of anxiety tests in laboratory rodents, while some of the side-effects of benzodiazepines or the GABA B receptor agonist baclofen, such as sedation, hypothermia, interaction with ethanol, or development of tolerance, were not observed with GS39783 [17,18]. Very similar results were obtained with other positive GABAB receptor modulators such as CGP7930 [20], ADX1441 [19] or BHF117 [24,27]. However, in some anxiety tests, the positive GABA B receptor modulators had no effects on anxiety-like behavior [18,20,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This was consistent with data obtained in adult mice of this mouse line [ 34 ]. Other studies involving a wide range of alterations in the GABAergic system have also not shown changes in fear learning [ 34 , 35 , 81 ]. In particular, knockdown of GAD67 in amygdala did not cause changes in cued fear conditioning [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…GABA plays an important role in reducing blood pressure, improving memory, and alleviating anxiety, due to its CNS inhibitory effects. [ 8,9 ] In Europe and the United States, GABA is considered as a “food constituent” and a “dietary supplement,” [ 10,11 ] respectively. GABA health products are patronized by a number of people, especially, the white‐collar working‐class women.…”
Section: Introductionmentioning
confidence: 99%